The Impact of Agricultural Extension Services on Female Farmers` Technical Efficiency: Evidence from Crop Producer Women in Uzbekistan - Mukhayo Djuraeva; Mashkhura Babadjanova; Abdulla Primov; Bekhzod Egamberdiev (ZBW - Leibniz Information Centre for Economics, 2025)
Extension services start to emerge in recent years but their impact on the production efficiency of women farmers is not empirically assessed in Central Asia. This paper investigates the role of extension services in improving female farmers' technical efficiency scores while analyzing the impact of farm characteristics explaining the efficiency differentials across female farmers in rural areas of Samarkand and Tashkent in Uzbekistan. Unique and primary cross-sectional data were collected during July and August 2022 for female crop-producing farmers. A sample of 145 female-headed farming entities was selected for the survey by using a multistage, random sampling technique. To analyze the data in the scope of our research objective, we used an endogenous stochastic frontier production function and calculated the technical efficiency score of the sampled female farmers. Our findings reveal that extension participation was found to be endogenously determined and was addressed through the best possible valid instruments – individual consulting, distance from the household to the main road, and distance to the main market. The analysis demonstrates that access to extension services and the number of visits of extension agents have a positive impact on technical efficiency levels among women crop producers. Moreover, analysis shows the positive impact of private extension services whereas state-managed extension agencies do not have a significant impact on production efficiency. Recognition of the determinants of women farmers' technical efficiency scores and the impact of extension services adoption ensures that targeted extension approaches should be encouraged and developed during the state policy reforms to address the existing gaps in resource-use management.
Keywords: N50; O13; D13; D24; 330; Agricultural extension services; female farmers; gender inclusivity; endogenous stochastic frontier model; crop productivity; Uzbekistan; Central Asia